GEREJA KRISTEN KALIMANTAN BARAT DALAM UPAYA MEMPERTEMUKAN DOGMA KRISTEN DENGAN TRADISI TIONGHOA - Joko Tri Haryanto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Development and disseminating of the Church of West Kalimantan Christians (GKKB) is based on Chinese descent people. The Chininese tradition is often understood as oposite to the Christian dogma which stressing on the purety of Christian faith and rational. GKKB succeeds to bridge the conflict and differences by using cultural strategy and the Chinese assembly accept it. This research was qualitatively in getting data to explore cultural strategy of the GKKB in developing of GKKB among the Chinese people. Two most used strategy of GKKB are acculturation between Chinese tradition with Christian dogma and christianizing of chinese tradition. Some of the tradition that opposing to the church are given value so it can be accepted as Christian. GKKB can survive with such strategy among the chinese tradition and Malay dominated culture of mayority other people.